The nativist prophets of early Islamic Iran: rural revolt and local Zoroastrianism - Crone, Patricia (Cambridge University Press, 2012)
"This learned and engaging study casts new light on the nature of religion in pre-Islamic Iran and on the persistence of Iranian religious beliefs both outside and inside Islam after the Arab conquest"--